LEGAL CONSIDERATIONS OF JUDGES IN APPLYING CRIMINAL SANCTIONS TO PERPETRATORS OF THE CRIMINAL ACTS OF MINING WITHOUT A PERMIT - Sandjaya, Alfath; Sujono (JILPR Journal Indonesia Law and Policy Review, 2025)
The judge's legal considerations regarding the criminal case of illegal mining in Decision Number 17/Pid.B/LH/2023/Pn.Tdn and Decision Number 119/Pid.Sus-LH/2024/PN.Tdn that the judge in sentencing the defendant is linked to the theory of the legal system, namely: the aspect of the legal structure has not been running optimally due to weak coordination between institutions, limited human resources and technology in supervising mining areas, and the presence of certain officers involved in corrupt practices that hinder the process of strict law enforcement. From the aspect of legal substance, Law Number 3 of 2020 concerning Amendments to Law Number 4 of 2009 concerning Mineral and Coal Mining does not clearly state the minimum sentence. Therefore, the judge is given the freedom to impose a sentence, unless the law specifically states the regulations that are at least, as short as possible, and as light as possible. From the aspect of legal culture, society is often still permissive towards illegal mining practices, especially in areas that depend on the mining sector as their main source of income. Therefore, legal reform in the mining sector must be carried out comprehensively so that criminalization can truly be an effective instrument in suppressing the number of illegal mining in Indonesia.